Reentrant condensation of a multicomponent cola/milk system induced by polyphosphate - Tomohiro Furuki; Tomohiro Nobeyama; Shunji Suetaka; Ryokei Matsui; Tatsuhiko Fukuoka; Munehito Arai; Kentaro Shiraki (Food Chemistry: X, 2024)
Reentrant condensation (RC) is a protein behavior in which the protein solution shifts between the one- and two-phase state more than twice by increasing a single parameter. Although RC would be a candidate mechanism for the physicochemical design of food additives, no realistic model has been established under diverse contaminants like food materials. Here, we found that a mixture of cola and milk yielded RC. At pH 3.2–3.6, cola induced milk condensation at 30–40%, while lower or higher concentrations of cola did not. Furthermore, we reduced this cola/milk system to two pure components, casein in milk and polyphosphate (polyP) in cola, and investigated the characteristics of casein concentration and zeta potential. This was the first experimental demonstration of RC occurrence in a multicomponent system. The well-characterized cola/milk system would explore both the universal nature of proteins and the industrial application of RC.